165: Profiles of Environmental Risk Impact Child Cognition Via Maternal Sensitivity and Human Capital Investments. Issue 6 (1st June 2014) - Browne, DT; Wade, M; Jenkins, JM
Abstract: BACKGROUND: There is evidence to suggest that socioeconomic status impacts neurocognitive functioning via family investment in child human capital. However, the role of parenting remains surprisingly equivocal, largely due to discrepancies in operationalization and measurement. Moreover, many studies examining the social determinants of cognitive development rely on simple metrics of socioeconomic status or risk. OBJECTIVES: The current study a) identifies multiple "family risk profiles" across several domains of adversity and b) examines the mediating role of human capital investments and sensitive maternal parenting behavior (coded from videotaped observations). DESIGN/METHODS: Family profiles of socioeconomic and contextual risk at two months of age were identified using participants from the Kids, Families and Places Study prospective birth-cohort. Subsequently, the impact of these profiles on child cognitive development via maternal sensitivity and human capital (material) investments was evaluated. Parents were contacted through a universal health screen seven days following childbirth (n=501) and followed until children were >4.5 years of age. RESULTS: Latent Class Analysis revealed that families fell into one of four profiles: 1) multilevel risk, 12.0% of sample, 2) maternal abuse history, 15.6%, 3) low-SES and immigrant status, 27.7% or 4) low-risk, 44.7%. Children in the multilevel risk and low-SES immigrant profiles had the poorest outcomes at 4.5 years. Between 35% and 56% of the effect of risk profile on cognitive outcomes was mediated by investments in child development, while 21% to 44% was mediated by maternal sensitivity, both measured at 18 months of age. CONCLUSIONS: Findings highlight the importance of material and interpersonal pathways through which socioeconomic and environmental disadvantage impact cognitive development. It will be argued that maternal sensitivity can be conceptualized as an alternative human capital investment, that is, a lived experience that promotes healthy development and successful adaptation across the life course.